2013
DOI: 10.1073/pnas.1315850110
|View full text |Cite
|
Sign up to set email alerts
|

Fast structural responses of gap junction membrane domains to AB5 toxins

Abstract: Gap junctions (GJs) represent connexin-rich membrane domains that connect interiors of adjoining cells in mammalian tissues. How fast GJs can respond to bacterial pathogens has not been known previously. Using Bessel beam plane illumination and confocal spinning disk microscopy, we found fast (∼500 ms) formation of connexin-depleted regions (CDRs) inside GJ plaques between cells exposed to AB5 toxins. CDR formation appears as a fast redistribution of connexin channels within GJ plaques with minor changes in ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Nevertheless, it can still address important biological questions 18,19 when the side lobe background is not a concern. The TP mode (TP Bessel beam plane illumination) offers high-speed and near-isotropic 3D resolution, but with limited multicolor capability 20 . It is the mode of choice for deep imaging, owing to the better penetration of its IR excitation in scattering and/or aberrating tissues.…”
Section: Implementing Multiple Scanning Beams To Reduce Photobleachinmentioning
confidence: 99%
“…Nevertheless, it can still address important biological questions 18,19 when the side lobe background is not a concern. The TP mode (TP Bessel beam plane illumination) offers high-speed and near-isotropic 3D resolution, but with limited multicolor capability 20 . It is the mode of choice for deep imaging, owing to the better penetration of its IR excitation in scattering and/or aberrating tissues.…”
Section: Implementing Multiple Scanning Beams To Reduce Photobleachinmentioning
confidence: 99%
“…Based on these findings, it was proposed that Cx43 hemi-channels are inserted into the general plasma membrane and quickly diffuse to the edge of GJ plaque, before slowly diffusing into the plaque center. Subsequently, it was observed that Cx43 can be inserted directly at the plaque and that membrane fluidity exists within the GJ space (Falk et al, 2009; Shaw et al, 2007; Majoul et al, 2013). Plaques can also be internalized from regions away from the plaque center, and that full GJ plaque internalization can occur in a single step (Falk et al, 2009; Piehl et al, 2007).…”
Section: Trafficking Highways To the Idmentioning
confidence: 99%
“…Advances in imaging speed, up to rates of hundreds of millions of volume elements per second, have enabled the design of light-sheet microscopes suitable for whole-brain functional imaging experiments at volumetric imaging rates that match the time scales of genetically encoded calcium indicators (Ahrens et al, 2013;Panier et al, 2013). Breakthroughs in spatial resolution-enabling up to 10-fold improvement in axial resolution and, therefore, isotropic spatial resolution on the order of 300 nm-have been demonstrated for single cells (Majoul et al, 2013;Planchon et al, 2011) and even small multicellular organisms (Gao et al, 2012;Wu et al, 2013). Advances in deep-tissue imaging and physical coverage of large biological specimens have been achieved through the introduction of multiphoton excitation in light-sheet microscopy (Truong et al, 2011) and through the implementation of light-sheet microscopes capable of imaging multiple complementary views of the sample simultaneously (Krzic et al, 2012;Schmid et al, 2013;Tomer et al, 2012).…”
Section: Light-sheet Microscopymentioning
confidence: 99%
“…Using live imaging approaches, light-sheet microscopes have been used to image dynamic processes over a wide range of spatial and temporal scales, from fast structural changes in the architecture of gap junctions (Majoul et al, 2013) and filopodial dynamics during axonal morphogenesis (Tomer et al, 2012) to whole-embryo imaging of C. elegans and D. melanogaster nervous system development with subcellular resolution (Tomer et al, 2012;Wu et al, 2011Wu et al, , 2013. In parallel to these efforts in the domain of developmental live imaging, several other groups developed strategies for structural wholebrain imaging, with a particular focus on rapid imaging of fixed and cleared mammalian brains (Dodt et al, 2007;Susaki et al, 2014;Tomer et al, 2014).…”
Section: Light-sheet Microscopymentioning
confidence: 99%
See 1 more Smart Citation